Professional exhaustion, quality and intentions among family health nurses - Vera Regina Lorenz; Marcos Oliveira Sabino; Heleno Rodrigues Corrêa Filho
ABSTRACT Objective: to analyze how family health nurses assess quality of care; check if they have any intention of leaving their current job and nursing; estimate prevalence of professional exhaustion; and correlate these variables. Method: cross-sectional and correlational study with 198 nurses. The Maslach Burnout Inventory was applied, as it has questions for characterizing nurses, assessing perception on quality of care and of material and human resources, and verifying intention of leaving current work and nursing. Results: most nurses assess quality of care as good, 28.0% present emotional exhaustion, there is intention of leaving current work and nursing. Conclusions: family health nurses experience professional exhaustion, which in turn presents correlation with decreased quality of care and increased intentions of leaving current work and nursing.